KEPEMIMPINAN KEPALA SEKOLAH, SUPERVISI AKADEMIK, KEEFEKTIFAN KOMUNIKASI, DAN PENERAPAN TOTAL QUALITY MANAGEMENT DI SMA - Wahed, Andi (Indonesian Journal of Educational Studies, 2015)
The research aims to determine the relationship between school leadership, academic supervision, and effectiveness of communication with the application of TQM. Research using quantitative approach. Data were collected using a questionnaire were then analyzed by using descriptive analysis and path analysis. The results showed leadership of the principal, academic supervision, the effectiveness of the communication and application of TQM is perceived by teachers with both categories. There is a direct relationship significant between school leadership with the application of TQM, there are no significant direct engagement between academic supervision with the application of TQM, there is a direct correlation between the effectiveness of the communication with the application of TQM, there is a significant relationship between the leadership of the principal with the effectiveness of communication, there is a relationship Significant among the academic supervision of the effectiveness of communication, there is no significant direct relationship between school leadership with the application of TQM through communication effectiveness, and there is not a significant direct relationship between academic supervision with the application of TQM through communication effectiveness.